Identifikasi Sikap dan Respon Emosional Siswa Saat Pembelajaran Matematika Berlangsung di SMP Negeri 7 Muaro Jambi - Revi Maria; Naila Salsabila; Hilda Nur Aini (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2026)
ABSTRAK The objective of this research is to pinpoint and articulate the emotions and attitudes of pupils while they study mathematics at SMP Negeri 7 Muaro Jambi. The study was prompted by the fact that some students continue to display unfavourable attitudes and unpleasant emotional responses toward mathematics education, including anxiety, fear, and a lack of self-confidence. A quantitative descriptive method was used in this investigation. 28 students who were chosen using a purposive sampling method made up the participant pool. Using a questionnaire with indicators of students' attitudes and emotional responses toward mathematics learning, data were gathered. The research results show that the obtained value is 2.462 out of the ideal value of 3.640, which is 67.6%, falling into the good category. This result shows that students' attitudes and emotional reactions during math learning still need to be improved. These results show that students' feelings and emotional reactions to learning mathematics still require improvement. Low self-confidence in completing mathematics tasks and anxiety when dealing with mathematics problems were identified as the main emotional responses. As a consequence, in order to cultivate more good attitudes and emotional responses toward mathematics, it is important to make attempts to establish a learning atmosphere that is more supportive and engaging.